Total and regional bone density in male runners, cyclists, and controls - Stewart, A. D.; Hannan, J. (Medicine & Science in Sports & Exercise, 2000)
. Purpose: Male athletes who were runners (N = 12), cyclists (N = 14), or both (N = 13) were compared with nonexercising age-matched controls (N = 23) for total and regional bone mineral density (BMD). All athletic subjects had competed for a minimum of 3 yr and trained for a minimum of 4 h·wk-1. Runners undertook no cycling and cyclists undertook no running training. Methods: All subjects were scanned for whole body and L1-L4 spine BMD using a Hologic QDR 1000W scanner (Hologic Inc., Bedford, MA). Results: There were no differences in age, height, weight, body mass index (BMI), % fat, or hours of training between any of the athletic groups (P > 0.05), although compared with controls, runners and cyclists had lower body mass index (P < 0.01) and all athletic groups had lower % fat (P < 0.001). Compared with controls, runners had greater total and leg BMD (P < 0.05), cyclists had reduced spine BMD (P = 0.05), and athletes of the "both" group had greater total (P < 0.05) and arm BMD (P < 0.01). Conclusion: Running is associated with increased bone density, particularly in the leg, whereas cycling is associated with a mild decrease in bone density in the spine. In athletes who do both, running exerts a stronger influence than cycling. Med. Sci. Sports Exerc., Vol. 32, No. 8, pp. 1373-1377, 2000.